REAL DRIVING EMISSIONS AND FUEL CONSUMPTION CHARACTERISTICS OF ISTANBUL PUBLIC TRANSPORTATION - Ozener, Orkun (VINCA INST NUCLEAR SCI, 2017)
Public transportation, which uses intro city lines frequently, has vital importance on the cities air pollution. The fossil fuel based drive units, which emits pollutants, are the primary source of this interest. Also, the fuel consumption is another major concern because of economic aspects. For an efficient and clear transportation, the pollutants and fuel consumption has to be analyzed, considering the operating conditions. In this context, the Metrobus line of Istanbul city which crosses from European side to Asian side of the city was analyzed with portable emission measurement system and portable fuel consumption meter devices. The relevant bus operating data were also collected during the operation. The data were analyzed while considering the operating modes like acceleration, deceleration, and constant speed cruises. The emission factors were developed. The pollutant emissions generally decreased as the vehicle speed increased while the fuel consumption increased for the same acceleration level. These results show the importance of operating conditions and their non-linear effect on emissions and fuel consumption Istanbul public transportation.
Keywords: real world emissions; fuel consumption; public transportation; BUSES; Thermodynamics